Political Culture and Media Genre - Richardson, K. author. aut Link
IX, 239 p.
Keywords: Exploring the forms and meanings of mediated politics beyond the news cycle, this book encompasses genres drawn from television, radio, the press and the internet, assessing their individual and collective contribution to contemporary political culture through textual analysis and thematic review.